Frequency Of Magnetic Resonance Imaging Findings In Patients With Lower Back Pain - wara, Kaif-ul; Zulfiqar, Taiba (Medical Science Journal for Advance Research, 2023)
Aims and objectives: To assess the MRI findings in patients who had lower back pain. Lower back pain affects most of the adults at some time in their lives. Background: The most common anomaly is lumbar disc degeneration, which can be caused by degenerative disc changes, narrowing of spaces in lumber spinal, cancer, infection, or trauma. In the evaluation of patients with lower back pain, Magnetic Resonance Imaging (MRI) has been the best modality to determine because this one is radiation free, non-invasive imaging modality with great both resolution (spatial and contrast).[1] Goal of this research was to find out the findings on MRI in patients who had lower back pain. Methods: This Descriptive cross-sectional study a total of 63 patients was conducted at the Radiology Department of Punjab Diagnostic Centre, Gujranwala, who had a lumbar spine MRI for severe and persistent lower back pain, radiculopathy, claudication (neurogenic) , or other symptoms and indications that could indicate low back discomfort. The age range of patients was 16 to 68 years. Non-contrast MRI scans was done. SPSS was used for statistical analysis. Magnetic Resonance Imaging (MRI) scan findings for patients who had lower back pain were determined. Results: Out of 63 patients there were (57.1%) 36 male patients and (42.9%) 27 female patients participated in this study. In Lumber spine straightening out of 63 patients in which there 23 patients (63.5%) noted (10) female and (13) male respectively. In 40 cases, the most well-known category was disc bulging at the L4/L5 level (63.4 percent) and L5/S1level was noted in 31 cases (49.1%) followed by L3-L4 level was noted in 11 cases (17.5%) in order of decreasing frequency. And Disc herniation was seen at total 16 patients (25.4percent) respectively. Disc herniation was more common at L4/L5 level. Disc desiccation was the most well-known category at L5/S1 in 35 cases (55.6%), L4/L5 level was noted in 24 cases (38.1%), L3/L4 level was noted in 14 cases (22.2%) and L2/L3 was noted in 7cases (11.1%) in order of decreasing frequency. Indentation of anterior theca was observed in 41.3% (26) of the total cases. In 76.2% (48) patients compression of the nerve root was seen out of total cases. Stenosis of the spinal canal was seen in 38.1% (24) out of the total cases.